2015
DOI: 10.1021/acs.jpcc.5b03969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si/Al Ratio and Rh Precursor Used on the Synthesis of HY Zeolite-Supported Rhodium Carbonyl Hydride Complexes

Abstract: Rh(CO) 2 complexes anchored on various dealuminated HY zeolites were used as precursors for the surfacemediated synthesis of Rh(CO)(H) x species. The carbonyl ligands of the initial Rh(CO) 2 complexes react with gas-phase C 2 H 4 to form Rh(CO)(C 2 H 4 ) species and subsequently well-defined Rh(CO)(H) x complexes when the former are exposed to H 2 at room temperature. Zeolite-supported Rh(C 2 H 4 ) 2 and Rh(NO) 2 can also be used as precursors, but both complexes must be converted into Rh(CO) 2 first to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 54 publications
4
70
2
Order By: Relevance
“…S8, S9, S10) provides a very clear visualization of the fact that NH3 is formed through the path involving hydrogen stored on Rh from water gas shift reaction. Molecular H2 in the gas phase does not catalyze the formation of ammonia, and thus Rh-H [28,29] rhodium hydride supported species are the important intermediate for NO hydrogenation, which we suggest can be formed through the recently uncovered carboxyl route [24]: Rh-OH + CO  Rh(COOH)  Rh-H + CO2. Hydride formed on rhodium, hydrogenates NO to ammonia at such notably low temperatures.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…S8, S9, S10) provides a very clear visualization of the fact that NH3 is formed through the path involving hydrogen stored on Rh from water gas shift reaction. Molecular H2 in the gas phase does not catalyze the formation of ammonia, and thus Rh-H [28,29] rhodium hydride supported species are the important intermediate for NO hydrogenation, which we suggest can be formed through the recently uncovered carboxyl route [24]: Rh-OH + CO  Rh(COOH)  Rh-H + CO2. Hydride formed on rhodium, hydrogenates NO to ammonia at such notably low temperatures.…”
Section: Resultsmentioning
confidence: 83%
“…Hydride formed on rhodium, hydrogenates NO to ammonia at such notably low temperatures. Although the very first supported transition metal carbonyl hydride complex was synthesized and comprehensively characterized for single rhodium(I) atoms in zeolite recently [28] starting with uniform Rh(I)(CO)2 zeolite-supported complex, no Rh-H complexes were reportedly identified for any other supported Rh material. Efforts are underway in our group to trap and characterize such species for Rh/Ceria system.…”
Section: Resultsmentioning
confidence: 99%
“…DFT provides remarkable agreement between the calculated and experimental frequencies for this complex. 18,52,54 Non-classical metal carbonyls have received attention in the organometallic literature. Due to pioneering efforts coming from the Aubke group, [19][20][21][22][23] for example, it was demonstrated that non-classical transition metal carbonyls can be produced from Pd or Pt compounds in toxic/corrosive magic acids HSO3F/SbF5 in the absence of moisture and under CO pressures.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding changes in the DR UV/Vis spectrum arise from a geometry change from tetrahedral to octahedral upon coordination of two pyridine molecules to a tetrahedral Co II center (Figure a) . FTIR spectroscopy studies upon the adsorption of 1 % NO pulse on the catalyst (Figure b) reveal the formation of mononitrosyl O 4 Co(NO) with ν(NO) at trueν˜ =1890 cm −1 , which is characteristic of metal nitrosyl complexes, and at higher NO pressures and in pure NO, cobalt dinitrosyl L 4 Co II (NO) 2 is formed with two characteristic ν(NO) bands at trueν˜ =1880 and 1795 cm −1 (Figure S9), which are essentially identical to the ones observed with Co II ions grafted into vacant T sites (pre‐emptied by special treatment) of zeolite Beta; also, molecular N 2 binds to the cobalt(II) center at 100 K (Figure c). This gives rise to a sharp ν(N−N) stretching band at trueν˜ =2282 cm −1 (both the IR spectra before and after N 2 adsorption are shown in Figure S10).…”
Section: Figurementioning
confidence: 97%